The unbearable bureaucratization of the Internet: The OSIPTEL’s proffer to regulate the “neutrality of red” in Peru - Zúñiga Palomino, Mario (2015)
This article analyzes the reasons for the so-called “network neutrality” and its regulation in Peru (including the laws regulating as a proffer recently presented by OSIPTEL); consisting primarily of equal treatment of all traffic, content or application by internet service providers. From Economic Analysis of Law’sperspective, it has been concluded that the Internet access does not present market failures that justify regulating the conditions of service provision. The author explains why network neutrality may have negative consequences for the internet access market in Peru.